Β‐Cell inflammation in human type 2 diabetes and the role of autophagy. (4th September 2013) - Marselli, L.; Bugliani, M.; Suleiman, M.; Olimpico, F.; Masini, M.; Petrini, M.; Boggi, U.; Filipponi, F.; Syed, F.; Marchetti, P.
Abstract : β‐Cell failure is crucial for the onset and progression of human type 2 diabetes, and a few studies have suggested that inflammation may play a role. Immune cell infiltration has been reported in subpopulations of islets in some cases of human type 2 diabetes, and altered gene expression of a few cytokines and chemokines has been observed in isolated islets and laser captured β‐cells from diabetic subjects. Recent observations on the links between inflammation, apoptosis and autophagy are putting the focus on the possibility that modulating the autophagic processes could protect the β‐cells from cytotoxicity induced by inflammatory mediators.